Determinação voltamétrica de ácido fólico em superfície de eletrodo sólido com filme intermetálico 'AG IND.2''HG IND.3.02': aplicação em sucos de frutas in natura e industrializados - Paula, Cleide Garcia de [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
In this work we developed na electroanalytical method on the surface of solid intermetallic electrode film Ag2Hg3.02 (AgSIE) for the determination of folic acid (FA). The AgSIE was used instead of liquid Hg electrode in order to attend to the concept of green chemistry . We applied the technique of square wave voltammetry toAdsorptive Stripping Voltammetry (SWAdSV), considering the analytical frequency selectivity and sensitivity of the method. The FA showed a peak reduction in -0,6 vs. Esce, with characteristics of adsorptive process. Optimized the experimental parameters and the analytical curves (n = 5) were constructed by diluting the standard solution in the range from 0.2 x 10-7 to 10.6 x 10-7 mol L- 1. The limits of detection and quantification were obtained for the FA LD = 6.79 x 10-10 mol L -1 and LQ = 2 x 10-8 mol L- 1, respectively. The standard addition method was used for determination of FA in folate pharmaceutical containing 5.0 mg / tablet , resulting in recovery of R % = 98.4  2.7% (mean = 4.9 ± 0 1 ) mg ( FAFI ), R = 99.9 %  2.9% (mean = 4.9 ± 0.15) mg ( FAFII ) and the multivitamin 0.25 mg / tablet : R % = 99.4  1.54 % ( m = 0.24 ± 0.03 ) mg ( FAFIII) and in samples of fruit juices in natura and processed , the concentrations from 0.3 to 84.4 mg L- 1 were obtained. The technique of High Efficiency Liquid Chromatography (HPLC), was utilized in the determination of FA in pharmaceutical and fruit juices for comparison, so the results was conducted in ODS - C18 column, 150 x 4.6 mm ( 5 m) mobile phase ACN / HAC-KOH, elution gradient (10:90, v / v ), pH 2.88, flow of 0.5 mL min -1 and UV-vis detector máx. 280 nm. The analytical curve (n = 3) of folic acid was built in the range from 1.41 x 10-6 to 4.53 x 10-5 mol L- 1 and calculated, LD = 8.38 x 10-8 mol L- 1 and LQ = 2.49 x 10-7 mol L- 1 . Accuracy was assessed pharmaceutical (5.0 mg / tablet ) for two dilutions 5:10 g mL -1, FAFI in obtaining the...

Neste trabalho desenvolveu-se um método eletroanalítico em superfície de eletrodo sólido com filme intermetálico Ag2Hg3.02 (AgSIE), para a determinação do ácido fólico (FA). O AgSIE foi utilizado em substituição ao eletrodo de Hg líquido de modo a atender ao conceito da “química verde”. Aplicou-se a técnica de Voltametria de Onda Quadrada Adsortiva de Redissolução (SWAdSV - do inglês: Square Wave Adsorptive Stripping Voltammetry), considerando-se a frequência analítica, seletividade e sensibilidade do método. O FA apresentou um pico de redução em -0,6 V vs. Esce , com características de processo adsortivo. Otimizou-se os parâmetros experimentais e as curvas analíticas (n= 5) foram construídas por diluição da solução padrão, no intervalo de 0,2 x 10-7 a 10,6 x 10-7 mol L-1. Os limites de detecção e de quantificação obtidos para o FA foram LD= 6,79 x 10-10 mol L-1 e LQ= 2 x 10-8 mol L-1, respectivamente. O método de adição de padrão foi aplicado para a determinação do FA em fármacos de ácido fólico contendo 5,0 mg/tablet, resultando numa recuperação de R%= 98,4  2,7 %, (m= 4,9 ± 0,1) mg (FAFI), R%= 99,9  2,9 %, (m= 4,9 ± 0,15) mg (FAFII) e para o multivitamínico de 0,25 mg/tablete: R%= 99,4  1,54 % (m= 0,24 ± 0,03) mg (FAFIII) e nas amostras de sucos de frutas in natura e industrializados, foram obtidas as concentrações de 0,3 a 84,4 g L-1. A técnica de Cromatografia Líquida de Alta Eficiência (HPLC - do inglês: High Performance Liquid Chromatography), foi utilizada na determinação de FA em fármacos e sucos de frutas para comparação dos resultados, assim, foi conduzida em coluna ODS-C18, de 150 x 4,6 mm (5 m), fase móvel de ACN/HAC-KOH, eluição por gradiente (10:90, v/v), pH 2,88, fluxo 0,5 mL min -1 e detector UV-vis máx. 280 nm. A curva analítica (n= 3) do ácido fólico, foi construída no intervalo de 1,41 x 10-6 a 4,53 x 10-5 mol L-1 e calculou-se...
Keywords: Quimica analitica; Ácido fólico; Suco de frutas; Voltametria; Eletrodos; Electrodes